Panphysics Enopiisis - Challoumis, Constantinos (Edelweiss Applied Science and Technology, 2024)
This paper examines Desmos (or Bond) and its implications compared to the literature review. It focuses on the parameter n, which characterizes how the effective force or interaction between celestial bodies changes with distance. By analyzing cosmic phenomena such as Mercury’s precession and Hubble's expansion, derived that variable n is approximately 1.10. This value indicates a deviation from the classical law, suggesting a more gradual weakening of forces with distance. Notably, the Bond model provides a different perspective on energy interactions, as it predicts higher effective energies for the Earth-Moon system compared to the Moon-Sun system, contrary to literature review predictions. In that way explains why the Moon is a satellite and not a planet, something that is not plausible to be explained in the current literature review. This finding aligns with observed cosmic expansion and offers a refined view of gravitational dynamics. Also, the elliptical forms on cosmos are the prove of rotation of gravity from desmos impact. Something that show the way to control and create gravity. Also, in that way is explained that there the dark matter is a space-time and energy effect from equations of Desmos (Bond).